2016
DOI: 10.1007/s00125-016-4110-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in liver fat by dietary MUFA in type 2 diabetes is helped by enhanced hepatic fat oxidation

Abstract: ClinicalTrials.gov NCT01025856 FUNDING : The study was funded by Ministero Istruzione Università e Ricerca and Italian Minister of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 11 publications
0
20
0
2
Order By: Relevance
“…33 Some recent studies 34,35 have shown long-term reduction of HFC and improvement in liver markers despite weight gain after dietary weight loss. Bozzetto et al 13,36 showed that an isocaloric diet enriched in monounsaturated fatty acids results in a reduction in HFC (by increasing fat oxidation), independent of weight change. In addition, the beneficial effect of different dietary strategies has been demonstrated in previous studies suggesting significant reductions in HFC with minor to moderate weight loss, 37 but this was not observed in larger, more recent studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Some recent studies 34,35 have shown long-term reduction of HFC and improvement in liver markers despite weight gain after dietary weight loss. Bozzetto et al 13,36 showed that an isocaloric diet enriched in monounsaturated fatty acids results in a reduction in HFC (by increasing fat oxidation), independent of weight change. In addition, the beneficial effect of different dietary strategies has been demonstrated in previous studies suggesting significant reductions in HFC with minor to moderate weight loss, 37 but this was not observed in larger, more recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…11 Diet plays an important role in the accumulation of HFC and VAT. 12 Several short- 6,13 and long-term 14,15 dietary interventions have suggested that Mediterranean and low-carb diets had favorable effects on VAT and HFC accumulation, but also on glycemic status and lipid biomarkers. Others found no differences between HFC changes induced by diets with different amounts of carbohydrate.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies considered it to be an HC diet if carbohydrate intake is over just 50% of total energy intake [34,35]. We guessed them as moderate carbohydrate diets (50%–54%), which were defined as HC diets in their studies, so we did not include them in this review [34,35]. On the other hand, the above-mentioned studies which were conducted in Asians generally set the standard of an HC diet as a carbohydrate intake over 60% of total energy.…”
Section: Literature About the Effects Of High Carbohydrate On Metamentioning
confidence: 99%
“…Although the evidence is rather convincing, the exact mechanism through which MUFA could affect hepatic triglycerides content is not completely clear. In both in vitro and in vivo studies, MUFA have been shown to activate peroxisome proliferator-activated receptor-alfa (PPARα) and PPARγ [ 56 ], increasing lipid oxidation [ 57 , 58 , 59 ] and inhibiting lipogenesis [ 58 , 60 ], thus leading to a reduction in hepatic steatosis ( Figure 2 ). On the other hand, MUFA can promote fatty acid deposition in adipose tissue rather than in the liver, enhancing the clearance of circulating triglyceride rich lipoproteins by lipoprotein lipase [ 61 ].…”
Section: Diet Composition and Non-alcoholic Fatty Liver Disease Inmentioning
confidence: 99%